A pregnant patient with a positive hepatitis B surface antigen. Issue 1 (31st August 2012) - Mufti, Arjmand Rasool; Reau, Nancy
Abstract : Hepatitis B is a major cause of liver disease worldwide. The highest rates of chronic infection occur in subjects who are infected early in life and these patients are also at the greatest risk of developing complications such as hepatocellular carcinoma and cirrhosis from the disease. There has been a concerted worldwide effort to immunise newborns that are at the highest risk of acquiring infection. In 1992, when WHO recommended global vaccination against hepatitis B, only 31 countries elected to participate in the programme. By 2009, 177 countries were part of WHO national infant immunisation programme. Consequently, maternal screening and infant immunoprophylaxis have significantly reduced vertical transmission of hepatitis B. In this paper, we will review the management of hepatitis B in the pregnant population and identify some of the challenges that are encountered in this specialised population.